A DEA model for evaluation of efficiency and effectiveness of sustainable transportation systems: a supply chain perspective. Issue 2 (27th October 2021) - Rajak, Sonu; Parthiban, P.; Dhanalakshmi, R.
The aim of sustainable supply chain management (SSCM) is to bring sustainability in every stage of the supply chain. Transportation is the key driver of logistics and supply chain management (SCM). In this context, this article presents a data envelopment analysis (DEA) method for the performance evaluation and selection of more efficient and effective transportation systems in the perspective of SSCM. This paper developed an integrated DEA enhanced Russell measure (ERM) model to select the best transportation systems provider. A model is used for the performance evaluation of the transportation system to minimise capital cost, cost of energy consumption, cost of work safety and labour's health, and CO2 emission. A numerical illustration has been presented, and sensitivity analysis is performed at different α levels to show the robustness of the proposed approach. The result shows that the proposed approach is practically applicable and capable of generating good quality solutions.